Risk and high school science: insight on student decisions about registering for advanced-level science classes - Thyren, John (My University, 2012)
The following study surveys students currently enrolled in advanced-level high school science electives in an attempt to discover what motivates these students to take such classes. Further, the study develops the argument that advanced-level science classes are a risky choice for students compared to offerings from other departments and makes an attempt to identify types of students who will be more likely to accept that risk. Findings suggest that, among other factors, college credit offered for such classes attracts students. Also, personality (as measured using the Meyers-Briggs Type Indicator) does play a role in a student's willingness to take science electives.
Plan B Paper. 2012. Master of Science in Education-Physics--University of Wisconsin-River Falls. Physics Department. 36 leaves. Includes bibliographical references (leaves 34-36).
Keywords: High school science electives; High school students--Attitudes; High schools--Curricula; Science electives; Physics--Study and teaching (Secondary)--Minnesota; Science--Study and teaching (Secondary)--Minnesota